Mechanically strong and folding‐endurance Ti3C2Tx MXene/PBO nanofiber films for efficient electromagnetic interference shielding and thermal management - Lei Wang; Zhonglei Ma; Yali Zhang; Hua Qiu; Kunpeng Ruan; Junwei Gu (Carbon Energy, 2022)
Abstract Electromagnetic interference (EMI) shielding materials with excellent flexibility and mechanical properties and outstanding thermal conductivity have become a hot topic of research in functional composites. In this study, the “sol–gel‐film conversion technique” is used to assemble polyetherimide‐functionalized Ti3C2Tx nanosheets (f‐Ti3C2Tx) with poly(p‐phenylene‐2,6‐benzobisoxazole) (PBO) nanofibers (PNFs), followed by dialysis and vacuum drying to prepare f‐Ti3C2Tx/PNF films with lamellar structures. When the loading of f‐Ti3C2Tx is 70 wt%, the f‐Ti3C2Tx/PNF film presents optimal comprehensive properties, with an EMI shielding effectiveness (SE) of 35 dB and a specific SE/thickness ((SSE, SE/density)/t) of 8211 dB cm2/g, a tensile strength of 125.1 MPa, an in‐plane thermal conductivity coefficient (λ) of 5.82 W/(m K), and electrical conductivity of 1943 S/m. After repeated folding for 10,000 cycles, the EMI SE and the tensile strength of f‐Ti3C2Tx/PNFs films still remain 33.4 dB and 116.1 MPa, respectively. Additionally, the f‐Ti3C2Tx/PNF film also shows excellent thermal stability, flame retardancy, and structural stability. This would provide a novel method for the design and fabrication of multifunctional composite films and considerably expand the applications of MXene‐ and PNF‐based composites in the fields of EMI shielding and thermal management.